2010
DOI: 10.1097/meg.0b013e32834059b6
|View full text |Cite
|
Sign up to set email alerts
|

Early and late outcomes of cardiac operations in patients with cirrhosis

Abstract: Cardiac surgery can be performed safely in patients with Child-Pugh class A and selected patients with Child-Pugh class B cirrhosis. Mid-term survival-rates within 8 years were not significantly different compared with a propensity-score pair-matched control group without cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Gundling et al . conducted an 8-year retrospective study and concluded that the necessity of blood product administration was increased in patients with liver cirrhosis undergoing cardiac surgery; the 30-day mortality rate was higher and long-term survival rate lower when compared to patients without liver cirrhosis 34 .…”
Section: Blood Transfusion In Complicated Cardiac Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gundling et al . conducted an 8-year retrospective study and concluded that the necessity of blood product administration was increased in patients with liver cirrhosis undergoing cardiac surgery; the 30-day mortality rate was higher and long-term survival rate lower when compared to patients without liver cirrhosis 34 .…”
Section: Blood Transfusion In Complicated Cardiac Patientsmentioning
confidence: 99%
“…Furthermore, recent reports have indicated worse outcomes when transfusion is due to preoperative anemia or blood dyscrasias 33 , 34 . In 2014, Engoren et al .…”
Section: Blood Transfusion In Complicated Cardiac Patientsmentioning
confidence: 99%